PROTEST VOTE: MITIGATING THE IMPACT OF SINGLE CANDIDATES IN LOCAL HEAD ELECTIONS - Ramadani, Rizki; Asriati, Asriati; Wahida, Wahida (Fakultas Hukum, Universitas Diponegoro, 2025)
In the 2024 local head elections, voters in 37 regions face a growing trend of single candidates. While voters can express dissent, the blank box option is often viewed as a mere procedural formality, with current regulations failing to address the negative impact of single candidates. This paper examines the protest vote as a form of voter engagement and explores its potential institutionalization as a solution to the single-candidate issue in local head elections. Using a normative approach, the research combines conceptual and legislative analysis, along with a qualitative review of existing literature. The protest vote, viewed from a political participation perspective, should not be seen as anti-political, but rather as a way for voters to voice dissatisfaction with the system or political elites. Few countries officially recognize the protest vote, but this study argues for its institutionalization through four measures: 1) ensuring the right to protest votes in local head elections, 2) recognizing blank, null, or spoiled ballots as valid votes, 3) defining empty boxes as